Acupuncture for the treatment of chronic obstructive pulmonary disease: a protocol of a systematic review. Issue 4 (28th April 2014) - Choi, Tae-Young; Jun, Ji Hee; Choi, Jun-Young; Kim, Jong-In; Lee, Myeong Soo; Ernst, Edzard
Abstract : Introduction: This review aims to evaluate the efficacy of acupuncture in the treatment of chronic obstructive pulmonary disease (COPD). Methods and analysis: 14 databases will be searched from their inception. These include PubMed, AMED, EMBASE, the Cochrane Library, seven Korean medical databases (Korean Studies Information Service System, DBPIA, Oriental Medicine Advanced Searching Integrated System, Research Information Service System, KoreaMed, The Town Society of Science Technology and the Korean National Assembly Library), three Chinese Databases (China National Knowledge Infrastructure Database (CNKI), the Chongqing VIP Chinese Science and Technology Periodical Database (VIP), and the Wanfang Database). Only randomised clinical trials (RCTs) using acupuncture for COPD will be considered. The selection of the studies, data abstraction and validation will be performed independently by two researchers. Methodological quality will be assessed with the Cochrane risk of bias. Dissemination: The systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print. Updates of the review will be conducted to inform and guide the healthcare practice and policy. Trial registration number: PROSPERO 2013: CRD42013004824.